Relationship between Dietary Fat-Sodium and Hypertension in Prolanis at Jarak Kulon Public Health Center - Heryanti, Wiwik Dwi; Rifa'i; Nahariani, Pepin; Kurdi, Fahruddin (Journal of Rural Community Nursing Practice, 2024)
Hypertension is a disease that causes high pain. Consuming sodium and fatty acids every day can increase the risk of hypertension. The impact of high fatty acids affects the presence of cholesterol deposits in the blood, while the levels of fatty acids cause increased blood pressure. This study aimed to analyze the relationship between sodium fat and hypertension in the Chronic Disease Management Program (Prolanis) at the Jarak Kulon Public Health Center Jombang. The research design used was cross-sectional. The population of this study was all hypertensive patients who participated in Prolanis, as many as 50 people. The sampling technique used was total sampling. The independent variable is the fat-sodium diet, and the dependent variable is hypertension. The instrument for the fat-sodium diet uses a questionnaire, while the incident uses observation. Statistical tests use Spearman Ranks. Spearman ranked data analysis with a significance of 0.01 and obtained a value of 0.000. Because (<α) means there is a relationship between the fat-sodium diet and hypertension. The test results also show that the relationship level of 0.695 is included in the strong category. Based on the research results, it is hoped that food content that is low in fat and low in sodium levels will help blood pressure to reach near-normal levels to avoid more severe complications.